The circRNA circSIAE Inhibits Replication of Coxsackie Virus B3 by Targeting miR-331-3p and Thousand and One Amino-Acid Kinase 2 - Yang, Qingru; Li, Yuhan; Wang, Yan; Qiao, Xiaorong; Liu, Tingjun; Wang, Hua; Shen, Hongxing (Frontiers in Cellular and Infection Microbiology, 2022)
Coxsackie virus B3 (CVB3), an enterovirus, is the main pathogen causing viral myocarditis, pericarditis, hepatitis and other inflammation-related diseases. Non-coding RNAs with a closed loop molecular structure, called circular RNAs (circRNAs), have been shown to be involved in multiple virus-related processes, but roles and mechanisms in CVB3 infection have not been systematically studied. In this study, when HeLa cells were infected with CVB3, the expression of hsa_circ_0000367 (circSIAE) was significantly decreased as demonstrated by real-time quantitative PCR assays. We found that circSIAE downregulated the expression of miR-331-3p through direct binding and inhibited the replication of CVB3 in HeLa and 293T cells. The analysis of signals downstream of miR-331-3p suggested that miR-331-3p promotes CVB3 replication, viral plaque formation and fluorescent virus cell production through interactions with the gene coding for thousand and one amino-acid kinase 2 (TAOK2). In conclusion, this study found that circSIAE can target TAOK2 through sponge adsorption of miR-331-3p to inhibit the replication and proliferation of CVB3 virus, providing an early molecular target for the diagnosis of CVB3 infection.